2017
DOI: 10.1186/s12974-017-1019-y
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effect of the latency-reversing agents bryostatin-1 and JQ1 on astrocyte-mediated neuroinflammation and brain neutrophil invasion

Abstract: BackgroundDespite effectiveness of the combined antiretroviral therapy, HIV-1 persists in long-lived latently infected cells. Consequently, new therapeutic approaches aimed at eliminating this latent reservoir are currently being developed. A “shock and kill” strategy using latency-reversing agents (LRA) to reactivate HIV-1 has been proposed. However, the impact of LRA on the central nervous system (CNS) remains elusive.MethodsWe used human fetal astrocytes and investigated the effects of several LRA on their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 64 publications
(68 reference statements)
2
26
1
Order By: Relevance
“…We have previously demonstrated that the LRA bryostatin-1 and JQ1 profoundly affect the physiology of human astrocytes (Proust et al, 2017). It was thus legitimate to assess whether treatment with bryostatin-1 and/or JQ1 can compromise the capacity of astrocytes to clear Aβ.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously demonstrated that the LRA bryostatin-1 and JQ1 profoundly affect the physiology of human astrocytes (Proust et al, 2017). It was thus legitimate to assess whether treatment with bryostatin-1 and/or JQ1 can compromise the capacity of astrocytes to clear Aβ.…”
Section: Discussionmentioning
confidence: 99%
“…They also induce oxidative stress in astrocytes, by binding to RAGE which induces ROS production via NOX complex activation (Askarova, Yang, Sheng, Sun, & Lee, 2011). Conversely, phagocytosis without degradation might provoke an intracellular accumulation that could cause inflammation, adding fuel to the inflammatory environment already established by HIV-1 and possibly enhanced by some LRA treatments (Proust et al, 2017). In addition, it has been shown that accumulation of Aβ protofibrils induces severe lysosome failure in the phagocytic astrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations